Extracellular cyclophilins A and C induce dysfunction of pancreatic microendothelial cells - Alvariño, Rebeca; Alfonso, Amparo; Pérez-Fuentes, Nadia; González-Jartín, Jesús M.; Gegunde, Sandra; Vieytes, Mercedes R.; Botana, Luis M. (Frontiers in Physiology, 2022)
Extracellular cyclophilins (eCyps) A and B are chemotactic mediators in several illnesses in which inflammation plays an important role such as diabetes and cardiovascular diseases. Recently, eCypC has been reported as a potential biomarker for coronary artery disease but its effect in endothelium has not been determined. Moreover, there is a lack of studies with all these proteins in the same model, which makes difficult a direct comparison of their effects. In this work, MS1 pancreatic microendothelial cells were treated with eCyps A, B and C and their impact on endothelial function was analysed. eCyps A and C stimulated the release of IL-6 and MCP-1 and increased the expression of the receptor CD147, but eCypB did not affect these pro-inflammatory markers. Moreover, eCypC activated the translocation of NFkB-p65 to the nucleus. All these effects were reversed by pre-treatment with cyclosporine A. eCyps also produced endothelial dysfunction, as evidenced by the decrease in eNOS activation. Finally, the crosstalk among eCyps addition and their protein and gene expression was evaluated. eCypA generated a depletion in its protein and gene levels, whilst eCyps B and C upregulated their own protein expression. Moreover, each eCyp altered the intracellular expression of other Cyps, including cyclophilin D. This work is the first report of eCyps influence on iCyps expression, as well as the first description of eCypC as an activator of CD147 receptor and a mediator of endothelial dysfunction, which points to a potential role of this protein in vascular complications associated to diabetes.